Affirmative Action at Work - McKillip, Jack (Education Policy Analysis Archives, 2001)
IMGIP and ICEOP are minority graduate fellowship programs sponsored by the State of Illinois in order to increase the number of minority faculty and professional staff at Illinois institutions of higher education through graduate fellowships, networking and mentoring support. Nearly 850 fellowships have been awarded since 1986. A performance audit examined immediate (areas of graduate study, ethnicity of awards), intermediate (graduation areas and rates), and long-range results (academic job placement). The primary source for the audit was the database maintained by the programs' administrative office. These data were compared with data sets maintained by the Illinois Board of Higher Education and with national benchmarks (NSF and Ford Foundation Minority Graduate Fellowships). Findings revealed: (a) the IMGIP and ICEOP programs led to major diversification of minority doctoral study in Illinois; (b) a high percentage of all fellows graduated, both absolutely and in relation to national benchmarks, and fellows made up a large percentage of doctoral degrees awarded to minorities by Illinois institutions (e.g., 46% of doctorates in the hard sciences awarded to African Americans from 1988-1998); and (c) fellows made up an important proportion of all minority faculty in Illinois (9%). Most ICEOP doctoral fellows and many other fellows have taken academic positions. The audit revealed outcomes-based evidence of a successful affirmative action program in higher educationevidence that is not otherwise available.